Transient Directing Groups in Metal−Organic Cooperative Catalysis. Issue 56 (18th August 2021) - Jacob, Clément; Maes, Bert U. W.; Evano, Gwilherm
Abstract: The direct functionalization of C−H bonds is among the most fundamental chemical transformations in organic synthesis. However, when the innate reactivity of the substrate cannot be utilized for the functionalization of a given single C−H bond, this selective C−H bond functionalization mostly relies on the use of directing groups that allow bringing the catalyst in close proximity to the C−H bond to be activated and these directing groups need to be installed before and cleaved after the transformation, which involves two additional undesired synthetic operations. These additional steps dramatically reduce the overall impact and the attractiveness of C−H bond functionalization techniques since classical approaches based on substrate pre‐functionalization are sometimes still more straightforward and appealing. During the past decade, a different approach involving both the in situ installation and removal of the directing group, which can then often be used in a catalytic manner, has emerged: the transient directing group strategy. In addition to its innovative character, this strategy has brought C−H bond functionalization to an unprecedented level of usefulness and has enabled the development of remarkably efficient processes for the direct and selective introduction of functional groups onto both aromatic and aliphatic substrates. The processes unlocked by the development of these transient directing groups will be comprehensively overviewed in this review article. Abstract : Strategic functionalization : The direct functionalization of C−H bonds is among the most important transformations in organic synthesis, but its efficiency depends on its selectivity, which can be controlled by the innate reactivity of the substrate or a directing group. While this last strategy has turned out to be efficient, the directing groups need to be installed before and cleaved after the transformation. These two undesired synthetic operations can be avoided by using the transient directing group strategy that is comprehensively overviewed in this review article.